2022
DOI: 10.3389/fonc.2022.766066
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Tyrosine Kinase Inhibitors Combined With Local Consolidative Radiation Therapy for Elderly Patients With Oligometastatic Non-Small Cell Lung Cancer Harboring EGFR Activating Mutations

Abstract: ObjectiveThe aim of this study was to investigate the efficacy and safety of combined applications of local consolidative radiation therapy (LCRT) and first-line tyrosine kinase inhibitors (TKIs) for the treatment of primary tumors and oligometastatic sites in oligometastatic NSCLC harboring Epidermal Growth Factor Receptor (EGFR) activating mutations.Patients and MethodsElderly patients with oligometastatic NSCLC (≤5 metastases) harboring EGFR activating mutations at the time of diagnosis were identified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Such a strategy has been shown as potentially beneficial in oncogene-addicted aNSCLC, but results of comparative prospective studies remain to be published. 29 In spite of these theoretical advantages, a minority of PD after DCB (4/43 – 9.3%) was treated with local therapies in our cohort (Supplementary Table S3). This might be due, to some extent, to the lack of follow-up data available at that time for clinician to support such treatments in PD after DCB.…”
Section: Discussionmentioning
confidence: 82%
“…Such a strategy has been shown as potentially beneficial in oncogene-addicted aNSCLC, but results of comparative prospective studies remain to be published. 29 In spite of these theoretical advantages, a minority of PD after DCB (4/43 – 9.3%) was treated with local therapies in our cohort (Supplementary Table S3). This might be due, to some extent, to the lack of follow-up data available at that time for clinician to support such treatments in PD after DCB.…”
Section: Discussionmentioning
confidence: 82%
“…In the eight studies that provided HRs, the pooled HR of median OS between the LT and TKI groups was 0.42 (95% CI: 0.36–0.48; P<0.001), which indicated a significant benefit in favor of the LT group, with a low heterogeneity (P=0.19; I 2 =30%) ( Figure 2B ). The median OS range in the LT group was 25.5 months to not reached, whereas in the TKI group, it was 17.6 to 60.0 months ( 36 , 37 , 39 , 40 , 43 - 46 ).…”
Section: Resultsmentioning
confidence: 91%
“…Funnel plot analyses were conducted to evaluate the potential reporting bias. The HRs of median PFS from all 11 studies were included, and HRs of median OS from the eight studies were also included in the funnel plot analyses ( Figure S2 ) ( 36 , 37 , 39 , 40 , 43 - 46 ). The funnel plots were symmetric, and Egger’s test values for them were 0.71 and 0.34, respectively, which indicated no apparent reporting bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the abovementioned study, regarding the complications of postablation, moderate pain was observed in 27 patients (38.0%), pneumothorax occurred in 23 patients, seven patients required chest tube drainage, nine patients had pleural effusion, of whom one required chest tube drainage, and 20 patients had postablation syndrome. There have also been several trials addressing the importance of IGTA in patients with NSCLC with oligoprogression 45–52 (See Table 1 for details). In fact, some studies have reported the relative mechanisms explaining why local ablation could prolong the PFS and OS of patients with oligoprogressive NSCLC with resistance to EGFR‐TKIs, and researchers have believed that local ablation could influence the EGFR/PI3K/AKT pathway, but a large sample size is needed to explore the detailed mechanism 53 …”
Section: Therapy For Oligoprogressionmentioning
confidence: 99%